THE IMPORTANE OF LEARNING ENGLISH IN A GLOBALIZED WORLD (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
In an increasingly interconnected world, learning English has become an indispensable skill. As globalization continues to shape global economies, cultures, and communication, English has established itself as the primary language for cross-border dialogue. It is the leading language in business, education, science, technology, and international diplomacy, enabling individuals and organizations to collaborate on a global scale. This article explores the reasons why learning English is essential in today’s globalized world. It delves into how English facilitates communication between people from different cultures, opens up career opportunities, provides access to academic resources, and enhances cultural exchange. Moreover, it highlights how English is pivotal in navigating the digital world and fostering global cooperation. Ultimately, this article emphasizes that learning English is not just a matter of academic achievement, but a key tool for success in personal, academic, and professional domains in a globalized society.